Portable spectrophotometer for water quality monitoring in recirculating aquaculture systems - Amijar, M I S M; Mohamed Ramli, Norulhuda; Khairudin, Nurulhuda; Abd Aziz, Samsuzana (Institute of Physics, 2024)
Water quality management in aquaculture is vital, as aquatic life is highly sensitive to changes in parameters such as inorganic nitrogen, pH, temperature, presence of gas, turbidity, and dissolved oxygen. The water quality must therefore be consistently monitored and controlled for the aquatic life to maintain optimum health, productivity, and quality. Currently, the problem arises when water quality analyses are time-consuming and could not be done rapidly. Thus, this project focused on designing a low-cost portable wireless spectrophotometer system for rapid water quality measurements. The hardware components used in the system consist of a C12880MA mini spectrometer chip, a Bluetooth module, and an Arduino Nano microcontroller. The microcontroller was programmed using the Arduino IDE environment and run by an Open-Source Miniature Spectrophotometer (OSMS) application. In this study, a portable wireless spectrophotometer that can measure water quality parameters such as turbidity is demonstrated. Water samples from the recirculating aquaculture system (RAS) were used to measure the water turbidity. The main objective of the study is to verify the applicability of the portable spectrophotometer for rapid and reliable water quality monitoring. Results showed that the spectrophotometer measurements had R2 of 0.94 when regressed on the turbidity of the RAS water samples. This showed that the customised portable spectrophotometer could be instrumental for a low-cost and rapid water quality monitoring in RAS.